1998
DOI: 10.1038/sj.mp.4000375
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide, neuroleptics and the ubiquinone and cytochrome b5 reductases in brain and lymphocytes from normals and schizophrenic patients

Abstract: The effects of the neuroleptic flupenthixol on the expression of the genes coding for the mitochondrial ubiquinone and cytochrome b 5 reductases have been studied because of the importance of these enzymes in energy metabolism, oxidative stress and also because similar but oppositely directed changes have been previously observed in the cerebral cortex from schizophrenics. The neuroleptic flupenthixol reduces the expression in rats of the gene coding for NADH-cytochrome b 5 reductase as measured by in situ hyb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 26 publications
(26 reference statements)
1
43
0
1
Order By: Relevance
“…[31][32][33][85][86][87][88] The results of this study extend this abnormality to bipolar disorder, whereby almost half of all significantly differentially expressed proteins identified were found to have a mitochondrial or other metabolic function. In the schizophrenia group, this figure was a quarter, suggesting that metabolic dysfunction in this area is relatively more prominent in bipolar disorder than schizophrenia.…”
Section: Discussionsupporting
confidence: 59%
“…[31][32][33][85][86][87][88] The results of this study extend this abnormality to bipolar disorder, whereby almost half of all significantly differentially expressed proteins identified were found to have a mitochondrial or other metabolic function. In the schizophrenia group, this figure was a quarter, suggesting that metabolic dysfunction in this area is relatively more prominent in bipolar disorder than schizophrenia.…”
Section: Discussionsupporting
confidence: 59%
“…However, these two lines of study are not consistent with each other since activity of complex IV was unchanged 63 or decreased 64 in the frontal lobes, while mRNA expression of complex IV increased in the frontal lobes, 62 putamen, 67 and nucleus accumbens 67 and decreased in the caudate. 67 Furthermore, antipsychotics decreased COII expression, while increasing COX activity.…”
Section: Schizophreniamentioning
confidence: 67%
“…Of these, increased levels of COII mRNA were confirmed in the frontal cortex of eight schizophrenic patients and five controls. 62 Increased COII was even more prominent in two drug-free schizophrenic patients, and the antipsychotic drug flupenthixol was found to decrease COII expression in experimental animals, suggesting that it was not drug-related. However, contrary to expectation, the activity of cytochrome c oxidase in the frontal cortex of patients with schizophrenia post-mortem did not show any alteration.…”
Section: Schizophreniamentioning
confidence: 99%
“…Thus, compared to healthy controls, complex I activity was significantly increased in patients in acute relapse and patients in a chronic active state but reduced in patients with residual schizophrenia. Reduced activities of complexes I and I-III have been previously reported in platelets and lymphocytes of chronic schizophrenic patients as compared with controls 14,17 and have been attributed to an inhibitory effect of antipsychotic drugs. [17][18][19][20] Indeed, a number of studies, including our own, have shown that antipsychotics inhibit complex I activity after chronic administration to rat or after in vitro addition to disrupted mitochondria.…”
mentioning
confidence: 99%
“…The etiology of schizophrenia is still unknown but recent advances in neuroscience have suggested a wide array of competing mechanisms that may be involved in the disorder, [3][4][5][6] among them altered cerebral energy metabolism 7 and mitochondria dysfunction. [8][9][10][11][12][13][14] Recently, we have shown that platelet mitochondrial complex I, which is the first complex of the mitochondrial electron transport system, is significantly increased in schizophrenic patients in the acute state, and not in patients with affective disorders. 15 In the present study we further demonstrate that complex I activity is altered with disease state presenting high specificity and sensitivity.…”
mentioning
confidence: 99%